EFFECT OF TAMOXIFFEN ON HEPATIC CELL OF FEMALS ALBINE MICE ON THE ELECTRON MICROSOPICAL STUDY - Alsalman, Maysoon (Iraqi Journal of Science, 2024)
The effect of tamoxiffen which used in the breast cancer treatment were studies on liver tissue of 10 females white mice,Both groups (control and treated)were drinked with(0.4 mg) for 90 days. Clanges in liver tissue were seen through the examination of tissue and studied at the cellular level.The study aims to identify the damage caused by drug tamoxiffen on the liver tissue and its effects for long period.